Biomarkers of response to advanced prostate cancer therapy. (1st February 2020) - Iacovelli, Roberto; Ciccarese, Chiara; Schinzari, Giovanni; Rossi, Ernesto; Maiorano, Brigida Anna; Astore, Serena; D'Angelo, Tatiana; Cannella, Antonella; Pirozzoli, Celeste; Teberino, Maria Anna; Pierconti, Francesco; Martini, Maurizio; et al.
ABSTRACT: Introduction : Prostate cancer (PCa) is one of the most common adult malignancies worldwide, and a major leading cause of cancer-related death in men in Western societies. In the last years, the prognosis of advanced PCa patients has been impressively improved thanks to the development of different therapeutic agents, including taxanes (docetaxel and cabazitaxel), second-generation anti-hormonal agents (abiraterone and enzalutamide), and the radiopharmaceutical Radium-223. However, great efforts are still needed to properly select the most appropriate treatment for each single patient. Areas covered : Several prognostic or predictive biomarkers have been studied, none of which has an established validated role in daily clinical practice. This paper analyzed the major biomarkers (including PSA, androgen receptor (AR) splice variants, βIII-tubulin, ALP, circulating tumor cells, and DNA repair genes) with a potential prognostic and/or predictive role in advanced PCa patients. Expert commentary : Surrogate biomarkers – measurable, reproducible, closely associated with tumor behavior and linked to relevant clinical outcomes – are urgently needed to improve PCa patient management.